The Key to Social Media Success Within Organizations - Kane, Gerald; Griffith, Terri; Elfenbein, Hillary; Orlikowski, Wanda; Shipilov, Andrew; Huy, Quy (MIT Sloan Management Review, 2012)
In this article, the authors show that although the use of social media can be an extremely valuable way to enrich a company's culture and enhance its productivity, it isn't a sure thing. Based on a survey of 1,060 executives about their experience with social media and a number of indepth qualitative case studies, the authors argue that the main reason some social media initiatives fail to bring benefits to companies is because the initiatives don't create emotional capital, which they define as a strong emotional connection between stakeholders and the company. In the end, social media is still media -- that is, mediums of communication -- and those new mediums can be used as badly and counterproductively as any traditional mode. To show how companies can create a winning strategy, the authors contrast the experiences of two companies -- an unnamed technology company and Tupperware Nordic, the Scandinavian branch of the kitchenware company. The technology company focused on software to facilitate social networking, not on using those new tools to build communities. It also tended to communicate in ways employees found insincere. Between insincere messages from the executive team and easier communication with other disgruntled employees, the initiative had no real positive effects for the company. Tupperware, by contrast, used the technology to help the company convey community spirit to its sales associates and took advantage of social media's unique ability to foster better vertical and horizontal communication. The authors conclude that although social media can help create closer and more dynamic stakeholder relationships, success with an online community requires a leader who can build emotional capital and who values community building as a means of creating economic value.